L’analyse de la dimension intime de l’activité scientifique d’apprentis-chercheurs en Sciences de l’éducation et de la formation (SEF) - Anne Bertin-Renoux; Jérôme Guerin (Éducation et Socialisation)
The emergence of an idea or the understanding of a phenomenon are regularly mentioned as a component of the researcher’s activity. However, these aspects are rarely mentioned in scientific communications as integral parts of the research process. This article reports an exploratory research conducted with apprentice researchers in education sciences in a doctoral seminar. Using an activity-based approach, the aim is to understand scientific activity « in the making » on the basis of real-life experiences. The objective is to reconstruct the process of emergence of ideas and conceptual transformations. These creative experiences are often informal moments that reveal an intimate part of scientific activity. By making the intimate dimension of scientific activity an object of study, the aim is to understand the way in which the apprentice researcher integrates and incorporates an epistemology relating to the activity.